The impacts of 5D-Building Information Modeling on construction's Time and cost performance - Hedy Herdyana; Agus Suroso (SINERGI, 2023)
The construction sector is essential to a country's economic growth and development. This is why the construction of building projects is one of the most pressing concerns for the Indonesian government. The industrial sector has become increasingly dynamic and responsive to the challenges of building projects due to technological advancements. One example is the Building Information Modelling (BIM) 5D, an emerging technology integrating project implementation time and costs into a 3D model. Therefore, this study aims to investigate the success factors of BIM 5D implementation on the time and cost performance of high-rise building construction projects at Campus-II UIN Sunan Ampel Surabaya. This was achieved through a quantitative research method using a questionnaire completed by 62 respondents: the project manager, site manager, engineering head, and site engineer. Moreover, descriptive statistics were utilized to examine the frequency distribution of concentration measures and data distribution on sample characteristics and variables. The findings showed that the factors of tender document, human resources, BIM software, planning process and production process simultaneously positively affected the construction project's cost and time performance.